Farmers’ Perceptions On Maize Ear Rots And The Prospects For Breeding Farmer Preferred Varieties In Uganda - Tembo, L.; Okori, P.; Asea, G.; Gibson, P. (In Proceedings of The Second RUFORUM Biennial Meeting, 2010)
Maize ear rots are a major constraint to maize production globally, and yield loses of up to 70% have been reported in Uganda. Developing varieties resistant to ear rots is a practical strategy that provides better insurance for the small scale farmers. To enhance the adoption of varieties, farmers’ perceptions should be included early in the breeding programme. In this study a survey was done in four districts of Uganda to examine farmers’ perception on ear rots and their views on agronomic desirable traits. High yield and earliness were the most preferred traits by the farmers.
Keywords: Fusarium, grain loss, Stenocarpella, Zea mays